Comparative Sequence, Structural and Functional Analysis of Interleukin-1 receptor-associated kinases (IRAKs) - GOSU, Vijayakumar (The Graduate School, Ajou University, 2015)
Interleukin-1 receptor-associated kinases (IRAKs) are Ser/Thr kinases in Toll-like receptors (TLRs) and interleukin-1 receptors (IL-1Rs) signaling pathways, which resides in cytoplasm and establish a connection between extracellular signaling detection and intracellular response. [1-3]. When a TLR ligand, as in the form of pathogen-associated molecular patterns (PAMPs), comes in contact with TLRs, these receptors respond by activating innate immune responses whereas, interleukin-1 receptor (IL-1R) family cytokine receptors senses the presence of ILs and activate the respective inflammatory mediators. Any anomaly in TLR signaling has been associated with several human diseases, such as infectious diseases, septic shock, autoimmune disorders, pro-cancerous and asthma [4-6]. TLRs homo/heterodimerize after detecting the ligand, several mediators such as MyD88, IRAKs, TRAF6, IκBs and NF-κBs are recruited to translate the signal to immune response. Among the mediator repertoire, IRAKs are the dire mediators owing to their kinase activity and adaptor functions. IRAKs initiate a cascade of signaling events in the intracellular region eventually leading to succumbing of invading threat involving the induction of inflammatory gene expression [7-9]. To highlight the importance of IRAKs, I have focused my doctoral research on addressing the following issues of IRAKs in TLR signaling. (i). IRAKs belong to serine/threonine kinase family. The human genome harbors 4 IRAK members (IRAK1, IRAK2, IRAKM and IRAK4). Each IRAK has specific downstream targets, and leads to a particular part of the TLR/IL-1R signaling pathway [10,11]. IRAK proteins are similar with respect to their domain organization, with a DD at N-terminal, a ProST domain, a centrally located KD, and a C-terminal domain (except for IRAK4, which are devoid of C-terminal domain) [3,12]. IRAK members are distantly conserved among species, and they have undergone remarkable sequence, structural, and functional divergence. Therefore, it was of high interest to formulate a hypothesis to trace the evolutionary history of IRAK family members. It has been elucidated using Phylogenetic relationships that IRAK4-like kinase might be an ancestral gene that diverged into other family members in the metazoan lineage. Further, our hypothesis suggested that the Tube protein is a homolog of IRAK4, unlike the anticipated protein, Pelle in insects [1]. (ii). IRAK4 is the principal kinase among IRAK members. IRAK4 kinase is of valuable therapeutic drug target in TLR signaling [13]. In IRAK4, kinase domain is initially autophosphorylated at T342, T345 and S346 [14]. However, data were unavailable regarding the inactive nature of IRAK4 KD [15] (before this work was published), and the regulation mechanism of IRAK4 kinase was vaguely clear. However the inactive crystal structure of IRAK4 KD has been published recently [15]. Therefore, we described the conformational changes in the IRAK4 KD among un-phosphorylated, phosphorylated and ATP-bound form by taking advantage of molecular dynamics simulation. Our results furnished that inactivation of IRAK4 kinase occurs when loses the interaction between R334 and T345, as well as R310 and T345. The Asp311 and Asp329 from catalytic HRD and DFG motifs involve in the catalytic mechanism of IRAK4 kinase. Profound motion during dynamics were observed for the unique structural motifs of IRAK kinase such as helix αC, αDE loop, helix αG and its adjoining loops [16]. (iii). In addition, we also focused on the evolutionary analysis of IκBs. This study proposed that ANK gene of Rel Homology Domain (RHD) might be the ancestor for all IκB family members. Further our structural and functional analyses supported that IκB family proteins undergo different physiological functions as well as distinct binding affinity for various NF-κB/Rel subunits [17]. We are currently focusing on understanding the binding modes of IRAK4 inhibitors and the complex stability using docking and dynamics simulations. And also research in my doctoral degree has instigated me to further examine the dynamic properties of IRAKM to understand its pseudo-kinase nature, and full length IRAK4 kinase, using long range molecular dynamics simulation.
학위논문(박사)--아주대학교 일반대학원 :분자과학기술학과,2015. 2
Keywords: Interleukin-1 receptor-associated kinases; IRAKs